ANALISIS YURIDIS BERCAMPURNYA HARTA WARISAN DENGAN HARTA PRIBADI DALAM HUKUM ISLAM : STUDI KASUS PUTUSAN PENGADILAN MAHKAMAH SYARI’AH BIREUEN NO. 297/Pdt.G/2012/MS-BIREUEN - FABRY ISMAN (PREMISE LAW JURNAL, 2016)
The dispute in inheritance in the Case No. 297/Pdt.G/2012/MS-BIR among the heirs occurred because of the delay in distributing it which causes the mixture of the inheritance with personal property of one of the heirs. the research showed that adat law recognizes and allows to delay the distribution of inheritance by certain reasons, but the Islamic law prohibits it because the mixture of inheritance with personal property will cause ambiguity in the inheritance, the rights of the other heirs are not in line with the Islamic law, and the legal act is legally defective in the third party. It is recommended that the Islamic society distribute inheritance by making inventory so that there will be no dispute n it. The Ruing of the Bireuen Sharia Court No. 297/Pdt.G/2012/MS-BIR has been in accordance with the prevailing rules in the Qur’an and Sunnah of the Prophet Muhammad and with the Indonesian national law. Keywords: The Mixture of Inheritance, Personal Property, Islamic Law